2015
DOI: 10.1002/oca.2186
|View full text |Cite
|
Sign up to set email alerts
|

Almost automorphic solutions for fractional stochastic differential equations and its optimal control

Abstract: Summary Fractional calculus is the field of mathematical analysis that deals with the investigation and applications of integrals, derivatives of arbitrary order. The strength of derivatives of non‐integer order is their ability to describe real situations more adequately than integer order derivatives, especially when the problem has memory or hereditary properties. This paper is mainly concerned with the square‐mean almost automorphic mild solutions to a class of fractional neutral stochastic integro‐differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Consider the Bolza problem false(trueP˜false) (see the works of Rajivganthi and Muthukumar, Yan and Xiumei, and Yan and Fangxia, which is to find an optimal pair false(x0,u0false)scriptB×Uad such that scriptJfalse(x0,u0false)scriptJfalse(xu,ufalse),uUad where the cost functional alignleftalign-1J(xu,u)=E0tγt,xtu,xu(t),u(t)dt+EΘ(xu(T)).align-2 …”
Section: Existence Of Optimal Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…Consider the Bolza problem false(trueP˜false) (see the works of Rajivganthi and Muthukumar, Yan and Xiumei, and Yan and Fangxia, which is to find an optimal pair false(x0,u0false)scriptB×Uad such that scriptJfalse(x0,u0false)scriptJfalse(xu,ufalse),uUad where the cost functional alignleftalign-1J(xu,u)=E0tγt,xtu,xu(t),u(t)dt+EΘ(xu(T)).align-2 …”
Section: Existence Of Optimal Controlmentioning
confidence: 99%
“…If not means, then there is nothing to prove. Using the assumptions (H7)‐(H12), we have alignleftalign-1J(xu,u)align-20TEw¯(t)dt+c10TExtuBdt+c20TExu(t)Cdt+c30Tu(t)Y2dt+Eθ(xu(T))align-1align-2ρ˜, where trueρ˜0 is a constant (see the works of Rajivganthi and Muthukumar and Tamilalagan and Balasubramaniam). Hence, ρ>trueρ˜>.…”
Section: Existence Of Optimal Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Ren et al [30] reported the existence and stability results of time-dependent stochastic delayed differential equations with Poisson jumps. Recently, Rajivganthi and Muthukumar [31] studied the properties of almost automorphic solutions of fractional stochastic evolution equations with Poisson jumps with the help of solution operator.…”
Section: Introductionmentioning
confidence: 99%